2016
DOI: 10.1515/cclm-2015-0954
|View full text |Cite
|
Sign up to set email alerts
|

The use of a “gray zone” considering measurement uncertainty in pharmacological tests. The serum growth hormone stimulation test as an example

Abstract: The use of a "grey zone" considering measurement uncertainty in pharmacological tests. The serum growth hormone stimulation test as an example.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Gray zones have been previously described for Aβ42/p-tau181 measured using INNOTEST ELISAs in patients with dementia, 43 and have also been described in recommendations for the use of CSF in the diagnostic workup of MCI patients. 44 Similar to other areas of medicine, including oncology and cardiology, [45][46][47] recommendations have included that the analysis be repeated or that an imaging-based investigation be performed. The upper and lower boundaries defining the gray zone for a given marker could even be used in the clinical chemistry laboratory providing the CSF results to clinicians, such that a gray zone result would result in immediate re-testing of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…Gray zones have been previously described for Aβ42/p-tau181 measured using INNOTEST ELISAs in patients with dementia, 43 and have also been described in recommendations for the use of CSF in the diagnostic workup of MCI patients. 44 Similar to other areas of medicine, including oncology and cardiology, [45][46][47] recommendations have included that the analysis be repeated or that an imaging-based investigation be performed. The upper and lower boundaries defining the gray zone for a given marker could even be used in the clinical chemistry laboratory providing the CSF results to clinicians, such that a gray zone result would result in immediate re-testing of the sample.…”
Section: Discussionmentioning
confidence: 99%
“…However, the guidelines do not refer to determining the grey zone in reporting illicit substances [14] . The current literature suggests using the grey zone approach to immunologically screen blood donors for infectious diseases and pharmacological tests (such as serum growth hormone stimulation tests) [5] [15] . Coste et al reported that using the grey zone approach in conjunction with the Bland-Altman method should increase reliability [16] .…”
Section: Discussionmentioning
confidence: 99%
“…Several guidelines and recent research have proposed replacing traditional immunoassay methods in urine illicit drug testing with more accurate tests, such as liquid chromatography-tandem mass spectrometry (LC-MS/MS) [15] [17] [18] . However, immunoassays are preferred in routine use for drug testing programs, as they provide rapid results.…”
Section: Discussionmentioning
confidence: 99%